Sistem Keamanan Server Linux CentOS Dengan Metode Port Knock dan RST Cookies - Muh. Adrian Juniarta Hidayat; Hadian Mandala Putra (Infotek: Jurnal Informatika dan Teknologi, 2023)
The increase in online-based services makes a security system for server computers increasingly needed. A server computer is a device that must always be available to be accessed anytime and anywhere. Some of the security systems needed for server computers include security for ssh port access for remote server access needs and a security system to protect servers from Denial of Service (DoS) attacks which can make the server down and completely inaccessible. In this study, a security system is proposed for a server computer with the Linux CentOS operating system on a port 22 secure shell(ssh) access system using the port knock method and a security system to prevent Denial of Service (DoS) attacks on server computers using the RST Cookies method. The simulation results from the port 22 Secure Shell (SSH) access experiment for the server computer can work well where port 22 Secure Shell(SSH) will remain closed and cannot be accessed carelessly except by accessing several ports first according to predefined port knocking rules. Likewise, the implementation of a security system with the RST Cookies method works very well to prevent Denial of Service (DoS) attacks and can still keep the server accessible with a good response time of under 1 ms